Validation of an HPLC Method for Determination of Bisphenol-A Migration from Baby Feeding Bottles. (28th March 2019) - Rodriguez, Ruth; Castillo, Elianna; Sinuco, Diana
Abstract : A simple and economic high-performance liquid chromatography (HPLC-UV-Vis) analytical method was validated for the quantitation of specific Bisphenol-A migration from baby feeding bottles. Overall and specific migration assays were done with different food simulating matrices using the filling method. Good linearity was obtained over the concentration range of 0.01–0.6 mg/kg. The limit of detection (LOD) and limit of quantification (LOQ) were 0.004 and 0.010 mg/kg, respectively. The repeatability of the method (%RSD, n = 10 ) was between 89.5 and 99.0%, while recovery ranged from 83.2 to 98.4%. The method was applied to specific migration assays from baby feeding bottles purchased from different plastic producers in Colombia. The results show that, in a first migration assay, Bisphenol-A was not detectable in all samples. In a second migration test, Bisphenol-A concentrations were higher than the most restricted limit (0.05 mg/kg) with ethanol 95% and isooctane as food simulants.